2010
DOI: 10.1055/s-0037-1619106
|View full text |Cite
|
Sign up to set email alerts
|

Clinical assessment of efficacy and safety of DDAVP

Abstract: Most adverse reactions were mild and no serious adverse drug reactions were either observed or reported by the subjects. We identified significant changes of heart rate, blood pressure and leucocytes after conduct of the DDAVP test. The value of these findings has to be investigated in later prospective randomized studies. Further research on identification of prospective parameter is currently ongoing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…A relatively high number of patients reported other side effects, often associated with preexisting complaints prior to infusion. This is a phenomenon also shown by Miesbach et al [4]. Therefore, we focused on patients without complaints at T0 to study the incidence of desmopressin-related side effects.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…A relatively high number of patients reported other side effects, often associated with preexisting complaints prior to infusion. This is a phenomenon also shown by Miesbach et al [4]. Therefore, we focused on patients without complaints at T0 to study the incidence of desmopressin-related side effects.…”
Section: Discussionmentioning
confidence: 86%
“…Despite this instruction we observed that 34% of patients drank more than 1.5 L. These patients did not differ with regard to laboratory values and vital signs or self‐reported side effects when compared to patients who drank <1.5 L. Lethagen et al . have used fluid restriction up to 2 L without severe side effects being reported . Patients tilted during infusion because of low BP or self‐reported dizziness, showed similar vital signs and water balance parameters after desmopressin to non‐tilted patients, suggesting that tilting is not indicative of hypotension or hyponatraemia after desmopressin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations